The effect of complex training and ballistic exercise on the time-course adaptations of lower extremity explosive strength in elite female field hockey players - Wang, Shuo; Jiang, Xianglong; Chen, Zitong; Xing, Xinyang; Zhang, Xiaofeng; Che, Tongtong (Frontiers in Public Health, 2025)
ObjectiveTo compare the short- and long-term effects of complex training (CT) and ballistic exercise (BE) on lower-limb explosive performance in elite female hockey players and to identify temporal adaptation patterns.MethodsTwenty-four athletes were randomized to CT (n = 8), BE (n = 8), or control (CG, n = 8). Interventions lasted 8 weeks (3 sessions/week). Performance outcomes included countermovement jump (CMJ), 30-m sprint, and squat 1RM, assessed at baseline, week 4, and week 8.ResultsAt week 4, the BE group improved CMJ (p < 0.01, d = 1.85), sprint (p < 0.01, d = 0.90), and 1RM (p < 0.05, d = 0.39), with no further gains by week 8 (p > 0.05). The CT group improved sprint (p < 0.01, d = 0.60) and 1RM (p < 0.01, d = 0.92) at week 4, while CMJ remained unchanged. By week 8, CT demonstrated significant improvements in CMJ (p < 0.05, d = 1.24), additional sprint gains (p < 0.01, d = 0.51), and continued 1RM increases (p < 0.01, d = 1.72). The CG declined in CMJ (p < 0.05, d = 0.44) and 1RM (p < 0.01, d = 1.03), with no sprint changes. Between groups, BE outperformed CG in CMJ at week 4 (p < 0.05). At week 8, both CT (p < 0.01) and BE (p < 0.05) exceeded CG in CMJ; sprint favored CT and BE over CG (p < 0.05); and 1RM favored CT over BE (p < 0.05) and CG (p < 0.01).ConclusionBE induces rapid short-term improvements in jumping and sprinting but plateaus after 4 weeks. CT produces slower yet sustained gains across all indicators by 8 weeks, with superior strength development. BE is suited for pre-competition phases, whereas CT is preferable during preparatory periods for integrated strength–power adaptation.